McAuley and Other Poets - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
James McAuley, Poetry, essays and personal commentary. Ed. Leonie Kramer. St. Lucia: University of Queensland Press, 1988. Running with Fire: An Anthology. Sydney: Round Table Publications, 1987. Procession:Young Street Poets 3. Ed. Fay Zwicky. Sydney: Hale & Iremonger, 1987. Dimitris Tsaloumas. Falcon Drinking. St. Lucia: University of Queensland Press, 1988.